Mongolia Economic Update : Navigating Stronger Headwinds - Fiscal Sustainability of the Mongolian Pension Scheme - World Bank (Washington, DC, 2022)
The report provides recent macroeconomic developments, outlook, and risks that Mongolia faces. The timing of the release of this report is ideal considering that, the Mongolian economy, which was recovering from the COVID-19 on the back of a successful vaccination program and income support, faced new challenges due to tightening of global financing conditions, triggered by a surge in inflation in advanced economies. This development complicates Mongolia’s repayment of its large external debt. Mounting instability and heightened risks call for adjustments in macroeconomic policies. The report also includes a special topic on fiscal sustainability of the Mongolian pension scheme. A series of parametric reforms are recommended to improve the financial sustainability of the current pensions system, which relies heavily on budget subsidy. Produced in collaboration with the SPJ team, this discussion was timely considering a forthcoming pension reform to improve Mongolia’s long-term fiscal sustainability.